INSTAGRAM SEBAGAI MEDIA DAKWAH (Analisis Isi Akun Instagram @harakah.id Bulan Muharram 1443 H) - Mohammad Asrovi; Agus Setyawan; Kha Fidhoh (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2023)
Innovating in preaching is something that is very important in responding to the challenges of the times. In modern times like this, sometimes people get bored with face-to-face da'wah models. In today's contemporary society, people must be approached with something that makes them interested. Social media has managed to achieve the highest popularity in the all-digital era, now one of the most loved by the global community today is Instagram social media. As a prestigious platform in this era. The emergence of Instagram social media which is widely used by various groups of people in communicating and exchanging information has not escaped the attention of da'wah activists to preach. Therefore, this research is a study that tries to describe the use of Instagram as a media for preaching the @harakah.id account. This type of research is descriptive qualitative research. To achieve the objectives of this study using the method of content analysis. While the data collection technique is done by observing and documenting. The data source used in this study uses the content @harakah.id uploaded in the month of Muharram 1443 H on Instagram regarding the use of persuasive communication from Mar'at and the theory of da'wah messages by Al-Bayanuni which divides da'wah messages in the aspects of faith, sharia and morals. The results of this study indicate that the da'wah messages in the @harakah.id account during the month of Muharram 1443 H contain 3 aspects, namely aqidah, sharia and morals. As well as the application of da'wah communication strategies on the Instagram account @harakah.id there are 2, namely rational preaching persuasive communication and emotional persuasion.